Implementasi UU Pemilu dalam Mempertahankan Keterwakilan Perempuan Paling Sedikit 30% pada Pencalonan DPR dan DPRD - Sufriaman, Sufriaman; Kursini Murham (Ikatan Ahli Informatika Indonesia, 2023)
Since the 2014 General Election, Indonesia has enacted rules on female representation with a minimum quota of 30 percent for legislative candidates and 30 percent women in the leadership of political parties as a form of affirmative action. These rules are claimed to have successfully encouraged an increase in the number of women's representation at the national level, although women's political participation in legislative bodies at the provincial and district levels generally remains low. Therefore, it is important to continue supporting the women's representation movement. We must ensure that women's rights are recognized and respected, that access to education, health, and economic opportunities increases, and that women have an equal role in decision-making at all levels. We must also continue to support and strengthen women's institutions and non-governmental organizations that advocate for gender equality, especially in achieving 30 percent female representation in parliamentary institutions. This research is descriptive in nature, focusing on uncovering a problem or situation as it is and providing an objective overview of the researched object. The research uses a normative doctrinal approach. Secondary data sources are used in this research, and data collection techniques include literature review or library research, which involves searching for and gathering relevant data and classifying it based on the juridical perspective found in literature and academic sources.